The First Treatment for PKU: The Pioneers-Birmingham 1951 - Anne Green (MDPI AG, 2021)
Prior to the introduction of newborn screening, Phenylketonuria (PKU) was a devastating disorder with affected individuals usually committed to a life in care in large institutions (asylums). Newborn screening only began after it was shown that those with PKU could be treated with a modified diet and could subsequently lead normal lives. The first production of a diet and the demonstration of its effectiveness was thus a key milestone in the history of both PKU and newborn screening, and took place in Birmingham, UK, in 1951. The pioneers were a two-year-old girl called Sheila Jones, her mother Mary, and three dedicated professionals at Birmingham Children's Hospital: Evelyn Hickmans, John Gerrard and Horst Bickel. Together, they changed the course of PKU for those across the world. This review summarises the history and achievements of this team who opened the door to PKU treatment and the introduction of newborn screening.